2019
DOI: 10.1093/intbio/zyz019
|View full text |Cite
|
Sign up to set email alerts
|

3D collagen architecture regulates cell adhesion through degradability, thereby controlling metabolic and oxidative stress

Abstract: The collagen-rich tumor microenvironment plays a critical role in directing the migration behavior of cancer cells. 3D collagen architectures with small pores have been shown to confine cells and induce aggressive collective migration, irrespective of matrix stiffness and density. However, it remains unclear how cells sense collagen architecture and transduce this information to initiate collective migration. Here, we tune collagen architecture and analyze its effect on four core cell-ECM interactions: cytoske… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 73 publications
0
33
0
Order By: Relevance
“…Lung cancer cells are able to bypass such mechanical inhibition through adapting their cytoskeleton and hence maintain high glycolytic rates while other cells in the TME cannot [ 116 ]. In general, the composition of the ECM has an impact on the cell’s metabolic phenotype and also impacts the adhesion and migration efficiency of cells [ 117 , 118 , 119 , 120 , 121 , 122 ].…”
Section: Constraints In the Tumour Microenvironment Determine Metamentioning
confidence: 99%
“…Lung cancer cells are able to bypass such mechanical inhibition through adapting their cytoskeleton and hence maintain high glycolytic rates while other cells in the TME cannot [ 116 ]. In general, the composition of the ECM has an impact on the cell’s metabolic phenotype and also impacts the adhesion and migration efficiency of cells [ 117 , 118 , 119 , 120 , 121 , 122 ].…”
Section: Constraints In the Tumour Microenvironment Determine Metamentioning
confidence: 99%
“…Stiffness of the extracellular matrix increased glycolysis in both cancer cells and cancer-associated fibroblasts [65]. Similarly, it has been shown that breast cancer cells and fibrosarcoma reduce glucose and glutamine uptake when grown in dense or crowded cellular matrices, and gene set enrichment analysis demonstrated an associated decreased expression of genes involved in the TCA cycle and pyruvate metabolism [66]. Morris and others demonstrated that a metabolic shift occurred in breast cancer cells grown in 3D gels with increasing collagen density, whereby oxygen consumption and glucose utilization by the TCA cycle decreased in high-density collagen gels [67].…”
Section: The Extracellular Matrix Induces Tumor Cell Intracellular Signaling Cascadesmentioning
confidence: 93%
“… 112 Further studies suggest that ECM microstructure regulates cell adhesion possibly through mediating matrix degradability, which is necessary for the cells to attach 3D collagen fibrils. 111 In addition, the regulation of Snail 1 and Notch signaling was found, indicating the emergence of collective cell behaviors. The fundamental understanding of the collective behavior of the cells (i.e., VM and alike) may lead to the rational design of biological systems that will fully utilize the power within the cells and ultimately benefit the biological modeling of development and disease.…”
Section: Emerging Areas In Engineering Biological Systemsmentioning
confidence: 98%